"Connecting online": The structure and content of students' asynchronous online networks in a blended engineering class. (April 2021) - Lee, Daeyeoul; Rothstein, Ruth; Dunford, Amy; Berger, Edward; Rhoads, Jeffrey F.; DeBoer, Jennifer
Abstract: Asynchronous online discussion has been widely used in higher education settings to create blended learning environments. Students form intricate social networks in asynchronous online discussions that promote help-seeking and help-providing. However, we know little about how students seek and receive help in asynchronous online discussions in blended engineering classes. This study employed a mixed-method approach by combining social network analysis and content analysis to describe students' interactions and help-seeking behaviors and to estimate their predictive power for academic performance on an asynchronous online discussion across several semesters of the same course. Social network analysis was performed to analyze the students' interactions, and content analysis was conducted to analyze the substance of their posts. The findings of this study showed variation in the structure of the social network across semesters, which is further explained by taking into account the content of the posts and the people present, both in class and online. There was a statistically significant difference in Asking for Answer Verification behavior between high-performing students and low-performing students in one semester. In addition, most of the students across all of the semesters were inclined to engage with the asynchronous online discussion by exhibiting Asking Technical Questions behavior. Based on the study findings, instructors should take on an authority role both in the classroom and on the online discussion forum itself and support students' help-seeking behaviors in asynchronous online discussions. Highlights: The structure of the social network in asynchronous online discussion varied across four semesters. The relationship between degree centrality and academic performance varied by semester. Students sought help in several different ways, and students provided help in a complementary manner. High-performing students showed Asking for Answer Verification behavior more than low-performing students in one semester. Most students across all semesters exhibited Asking Technical Questions behavior.